Bioclimatic Design Strategies for Optimizing Natural Ventilation Calculation for Low-cost Housing: Simulation of Window Placement, Size, and Building Orientation - Wijaksono, Sigit; Suyadi, Dedi (Talenta Publisher, 2025)
This paper presents a study of the implementation of bioclimatic architecture that can provide a good air circulation created from using natural ventilation. Natural ventilation is the process of exchanging air inside the building through the help of open building elements. The background of this study is nowadays architectural development for low – cost apartment in Indonesia doesn’t support good natural ventilation, people start to build something that will benefit in the market and ignore the importance of the good air circulation. So, promoting and applying the natural ventilation as a part to low – cost energy consumption and avoid sick building syndrome with good air circulation especially after pandemic corona virus become importance issue. The research method used is descriptive quantitative method, in the form of research with a case study approach and simulation. The result achieved is that the building can optimize natural ventilation evenly through orientation, building shape, opening design, etc. It is expected that the flat with the bioclimatic concept can respond to the climate by designing passively.